2021
DOI: 10.1088/1402-4896/ac217f
|View full text |Cite
|
Sign up to set email alerts
|

High quality factor multichannel filter of electrons based on defective CdMnTe/CdTe multi-quantum wells

Abstract: Using the transfer matrix (TM) method, the propagation of electrons is studied, in a one-dimensional multi-quantum well composed of alternating layers of barriers and wells. In the first time, we proposed system with a single barrier CdMnTe is embedded between two semi-infinite substrates. Hence, the corresponding Eigen modes energies were found to be shifted towards lower energies as the barrier thickness increases. The resulting Eigen modes are characterized by a high transmission rates but a very low qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…We can also see that when the thickness of the barrier d1 increases, the number of electronic states increase and move towards high energies. This last result is similar to the one found by Ezzarfi et al when they considered a finite CdMnTe semiconductor between two substrates of the same nature [25]. When the energy of the incident electron coincides with one of the electronic states, the electron is completely transmitted.…”
Section: Resultssupporting
confidence: 89%
“…We can also see that when the thickness of the barrier d1 increases, the number of electronic states increase and move towards high energies. This last result is similar to the one found by Ezzarfi et al when they considered a finite CdMnTe semiconductor between two substrates of the same nature [25]. When the energy of the incident electron coincides with one of the electronic states, the electron is completely transmitted.…”
Section: Resultssupporting
confidence: 89%
“…I. Erdogan et al [8] have studied the effect of laser field on the self-polarization of a donor impurity in a finite Ga1-xAlxAs/GaAs quantum well. Furthermore, we find other researchers who studied the band structures and even the electron transport in MQWs by determining their physical properties (transmission, reflection, dispersion relation ...) using the Green's function [9], or the transfer matrix [10]. For example, we find that A. Shokri [11] studied a periodic MQWs, composed of two alternating materials, GaAs-AlGaAs.…”
Section: Introductionmentioning
confidence: 85%
“…They showed that the thickness and concentration of the defect layer have an impact on the electronic states localized in the band gap [14]. They also studied the propagation of electronic wave in one-dimensional multi-quantum well composed of alternating layers of barriers and wells using the transfer matrix (TM) method, they showed that as the barrier thickness increases, the energies of the corresponding Eigen modes shift to lower energies [15]. Moreover, the transfer matrix method (TMM) is classically used to predict acoustic properties, the transmission was determined using the Transfer Matrix Method (TMM) algorithm, the pressure P can be described in one-dimensional direction (following x for example) as:…”
Section: Theoretical Formalism: Transfer Matrix Methodsmentioning
confidence: 99%